A Simplified CMV-specific T Cell Transfer Targeting Drug-resistant CMV Retinitis. (18th August 2022) - Mo, Wenjian; Liang, Yuqin; Wang, Caixia; Zhang, Yuehong
ABSTRACT: Background: Among severely immunosuppressed patients resistant or refractory cytomegalovirus (CMV) retinitis is not uncommon, and is potentially blinding in the affected eye. Immunotherapy using CMV-specific cytotoxic T lymphocytes (CTLs) is an emerging and promising alternative for the control of resistant or refractory CMV retinitis. However, highly purified CMV-CTLs are still not available in the majority of medical institutions in China because the generation of CMV-CTLs is labor intensive, time-consuming and expensive. Purpose: This letter describes the clinical responses to a simplified CMV-CTL immunotherapy aimed at controlling drug-resistant CMV retinitis in two immunodeficient patients. Conclusions: Our cases suggest that the simplified CMV-CTL immunotherapy offers a highly efficient and low-cost solution to drug-resistant CMV retinitis. This immunotherapy strategy targeting drug-resistant CMV retinitis is likely to be cost-effective in the context of a specific patient population.